Partner Abuse of Mothers Compromises Children's Behavioral Functioning Through Maternal Mental Health Dysfunction: Analysis of 300 Mother‐Child Pairs. Issue 2 (23rd December 2015) - Maddoux, John A.; Liu, Fuqin; Symes, Lene; McFarlane, Judith; Paulson, Rene; Binder, Brenda K.; Fredland, Nina; Nava, Angeles; Gilroy, Heidi
Abstract: Partner violence is associated with numerous negative consequences for victims, especially poor mental health. Children who are exposed to partner violence are more likely to have behavior problems. Nevertheless, research on the relationship between severity of abuse, maternal mental health functioning following partner violence, and child behavior problems is limited. We explored the direct and indirect effects on the child's behavioral functioning of severity of maternal abuse and maternal mental health functioning following abuse. A sample of 300 mothers was recruited when they sought assistance for abuse for the first time at shelters for abused women or at the district attorney's office. Severity of abuse, mothers' mental health functioning, and child behavioral functioning were measured by maternal self‐report at entry into the study and 4 months later. In SEM analysis, at both entry and 4 months, severity of abuse had a direct effect on maternal mental health functioning, which in turn had a direct effect on child behavioral functioning. The path from severity of abuse to child behavioral functioning also was significant but became non‐ significant once maternal mental health functioning was added to the equation, indicating that the path from severity of abuse to child behavioral functioning was indirect and occurred as a result of the mother's mental health functioning, which remained directly linked to child behavioral problems. Intergenerational interventions are needed to address both maternal mental health and child behavioral functioning when a mother reports partner violence and is experiencing mental health problems. © 2015 Wiley Periodicals, Inc.